Preconditioning in the Backtracking Duty Generation of Passenger Rail Crew Scheduling: A Case Study - Koniorczyk, Matyas; Talas, Borbala; Gedeon, Ferenc (Communications - Scientific letters of the University of Zilina, 2015)
We describe briefly the crew scheduling and rostering approach implemented in Railm@n, the system used by MAV START, the passenger railway transport company of Hungary, to organize the work of passenger train crews that is, conductors. Then we discuss the scheduling (duty generation) phase of the algorithm in detail. When treated in full generality, the problem already scales to an untractable size. We describe our successful experience with the use of preconditioning to keep the problem tractable. The approach may be useful in timetable planning and depot planning, too.